2002
DOI: 10.1007/bf03020526
|View full text |Cite
|
Sign up to set email alerts
|

Active warming of saline or blood is ineffective when standard infusion tubing is used: an experimental study

Abstract: Purpose: To determine the effect of infusion rate, tubing length and fluid composition on the temperature of the infusate reaching the distal end of an infusion tubing with and without active fluid warming.Methods: Warmed normal saline (W-NS) and packed red blood cells (W-PRBC), were infused with a fluid warmer through a modified infusion set. The fluids were delivered at eight infusion rates from 50 to 999 mL·hr -1 . The infusate temperature was monitored at 20 cm intervals on the iv tubing. The same temperat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
19
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 22 publications
0
19
0
1
Order By: Relevance
“…The enFlow device is capable of warming both room temperature-and cooled fluid at all the flow rates tested, making it a more flexible device for the operating theatre setting. Tubing length has a profound influence on the fluid temperature entering the patient [5,8]. Doublewalled infusion lines with coaxial flow around the infusate maintain the warming effect along the length of the tubing.…”
mentioning
confidence: 99%
“…The enFlow device is capable of warming both room temperature-and cooled fluid at all the flow rates tested, making it a more flexible device for the operating theatre setting. Tubing length has a profound influence on the fluid temperature entering the patient [5,8]. Doublewalled infusion lines with coaxial flow around the infusate maintain the warming effect along the length of the tubing.…”
mentioning
confidence: 99%
“…Heating using a blood warmer results in hemolysis. Heat loss along the intravenous line is a serious problem in the use of heated fluids (11)(12)(13).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that fluid warmers are usually unnecessary in adults below a flow of 35 ml.min À1 , which reduces the core body temperature by less 0.5°C, although the effect depends upon body mass [6,8]. Infusate heat loss increases with the length of the intravenous line [10,11,[15][16][17]. Short lines can be used with the warmers we studied as they are small and can be positioned close to the patient.…”
Section: Discussionmentioning
confidence: 99%
“…Infusate heat loss increases with the length of the intravenous line [10,11,[15][16][17]. Short lines can be used with the warmers we studied as they are small and can be positioned close to the patient.…”
mentioning
confidence: 99%